The use of probiotics in the diet of farmed South African abalone Haliotis midae L - Maliza, Siyabonga (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2015)
Physiological stress in farmed abalone can lead to immunosuppression and increase the susceptibility to bacterial, viral and parasitic disease, often followed by mortality. Thus, handling and poor water quality can reduce farm production efficiency. Probiotics in aquaculture have been effective in a wide range of species in enhancing immunity, survival, improving feed utilisation and growth. Three putative probionts identified as a result of in vitro screening had been beneficial to laboratory-reared abalone in a previous study. The aim of this study was to produce an abalone feed that contains a suite of probionts that may promote abalone growth and health under farming conditions. The objectives were to compare growth and physiological responses (i.e., haemocyte and phagocytosis counts) of abalone fed a commercial feed (Abfeed®S 34, Marifeed, Hermanus) supplemented with probiotics (i.e., the probiotic diet) to abalone fed the commercial feed without probiotic supplementation as a control treatment in a factorial design with handling method as an independent variable. This experiment was conducted at HIK Abalone Farm (Pty Ltd) for a period of eight months with initial weight and length 36.1 ± 0.05 g and 58.6 ± 0.06 mm abalone-1. Another experiment was carried out at Roman Bay Sea Farm (Pty) Ltd with initial weight and length 34.7 ± 0.17 g and 62.3 ± 0.18 mm abalone-1, but this experiment included one factor only, i.e. the presence and absence of the probionts in the feed. At HIK there was no significant interaction between diet and handling on average length and weight gain month-1 after four (p=0.81 and p=0.32) and eight (p=0.51 and p=0.53) months, respectively. Average length (additional handling = 73.9 ± 0.52 mm, normal farm handling = 75.8 ± 0.57 mm) and weight gain (mean: additional handling = 68.5 ± 1.20 g, normal farm handling = 74.3 ± 1.86 g) increased significantly in animals that were handled under normal farm procedure and were either fed probiotic or control diet after eight months (p=0.03 and p=0.02, respectively). There was no iii difference in length gain or weight gain of abalone fed the probiotic diet and those fed the control diet (ANOVA: F(1,16)=0.04, p=0.84; F(1,16)=0.14, p=0.71, respectively). After four months phagocytotic count was significantly different between dietary treatments with mean values of 74.50 ± 10.52 and 63.52 ± 14.52 % phagocytosis count per sample for the probionts and control treatment, respectively (p=0.04), there was no difference after eight months at HIK Abalone Farm. There was no effect of stressor application (p=0.14) and no interaction between dietary treatment and stressor application for this variable i.e., phagocytosis count (p=0.61). There was no difference in feed conversion ratio between treatments with values ranging from 2.9 to 3.8. At Roman Bay Sea farm, there was no significant difference in mean length gain between abalone fed the probiotic and control diet after eight months (repeated measures ANOVA: F(4,28)=16.54. Mean weight gain of abalone fed the probiotic diet was significantly greater than those fed the control diet after eight months (repeated measures ANOVA: F(4,28)=39.82, p(0.00001). There was no significant difference in haemocyte counts between animals fed either probiotic or control diet after four and eight months at Roman Bay Sea farm (p>0.05).
Keywords: Haliotis midae -- South Africa; Abalones -- South Africa; Haliotis midae -- Feeding and feeds; Haliotis midae -- Effect of chemicals on; Haliotis midae -- Growth; Haliotis midae -- Immunology; Probiotics